Pelatihan Inovasi Pembelajaran Vokasional Berbasis Artificial Intelligence untuk Komunitas Guru Sekolah Menengah Kejuruan Kalimantan Utara - YOGA SAHRIA; Putu Sudira; Satriyo Agung Dewanto (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2026)
Teachers in Sekolah Menengah Kejuruan located in remote and underserved districts of North Kalimantan Province face a widening gap between national policy demands for Artificial Intelligence adoption in vocational learning and the limited digital literacy and technological infrastructure available at the school level. This community service program was carried out to strengthen Artificial Intelligence literacy, pedagogical competence, and instructional innovation among vocational teachers affiliated with three partner schools, namely State Vocational School 2 Malinau, State Vocational School 1 Malinau, and the State Agricultural Vocational School of Malinau, in Malinau Regency, North Kalimantan. The program adopted a participatory training and mentoring approach comprising needs assessment, conceptual reinforcement on Artificial Intelligence fundamentals and ethics, hands-on workshops on prompt writing and the use of generative Artificial Intelligence for lesson design, teaching media, and assessment, followed by post-training evaluation. Evaluation data were collected from thirty-two participating teachers using a twenty-item closed questionnaire covering five dimensions, namely Artificial Intelligence literacy, teacher competence in Artificial Intelligence-based instruction, training implementation, vocational learning innovation, and program benefit and sustainability, complemented by five open-ended reflective questions. Results showed an overall mean score of 4.48 out of 5, equivalent to 89.7 percent of the maximum score, with twenty-four of thirty-two teachers, or seventy-five percent, classified in the very good category. The training implementation and innovation dimensions recorded the highest scores, while qualitative findings highlighted unstable internet connectivity, restricted access to paid Artificial Intelligence applications, and strong demand for continued, more intensive hands-on mentoring as dominant themes. The program demonstrates that structured, practice-based training can rapidly elevate vocational teachers' readiness to integrate Artificial Intelligence, provided that infrastructural and sustainability barriers are addressed through continued institutional support.